Analisis Perilaku Wisatawan Berdasarkan Data Ulasan di Website Tripadvisor Menggunakan CRISP-DM: Wisata Minat Khusus Pendakian Gunung Rinjani dan Gunung Bromo - Yerik Afrianto Singgalen (Journal of Computer System and Informatics (JoSYC), 2023)
Traveller behavior needs to be comprehensively identified and analyzed to determine changes in tourism preference in Indonesia. One relevant approach to identifying traveler behavior is sentiment analysis through review data on the Tripadvisor website by text mining approach. This study aims to recommend a sentiment analysis model that is useful for managers of particular interest climbing tourist destinations on Mount Rinjani and Mount Bromo based on the type of visit alone (solo), with couples (couple), with friends, and with family (family). The research method used is Cross Industry Standard Process for Data Mining (CRISP-DM), with an algorithm adapted to managing tourist destinations for Mount Rinjani and Mount Bromo, namely attractions, roads and modes of transportation (accessibility), and accommodation. To overcome the problem of data balance in datasets, the calculation process of the Decision Tree (DT) algorithm and the Support Vector Machine (SVM) is connected to the Synthetic Minority Over-sampling Technique (SMOTE) operator in the Rapidminer application. The results of this study showed that the SVM algorithm showed better performance with an accuracy value of 97.67%, precision of 100%, recall of 95.34, and f-measure of 97.61% in the classification of 1075 text data of Mount Bromo and 326 review data of Mount Rinjani. In addition, in the context of Mount Rinjani, the top five words that often appear in tourist review data on Mount Rinjani are as follows: summit (272), Rinjani (259), trek (201), hike (170), mountain (159). On the other hand, the top five words that often appear in tourist review data on Mount Bromo are as follows: Bromo (1864), sunrise (1124), view (854), crater (758), and mount (577). Thus, it can be seen that tourists with the type of visit alone (solo), with couples (couple), with friends (friends), and with family (family) have a preference for the types of attractions in the form of summits, craters, natural beauty of mountains, hiking trails, types of transportation modes as well as supporting accommodation that needs to be prepared to keep the sustainability of tourism.